(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: For larger Renal Cell Carcinoma (RCC), partial nephrectomy (PN) is gaining its feasibility, which facilitates conservation of functional renal tissue but keeping oncological outcome unaltered. Our aim is to study the short term i.e. one year oncological and renal functional outcome of > 7 cm RCC cases treated with PN. Methodology: A descriptive, prospective, observational study was designed and cases of RCC with size >7 cm, favorable anatomy, treated with PN were included. Preoperative and post-operative renal function, tumor characteristics, oncological clearance, cancer recurrence and post-operative complication were studied by following up for 12 months. Result: Total 22 patients was enrolled, 86.4% were male, mean age 58.73 + 6.69 years, mean BMI 24.34 + 2.7 kg/m2 and 02 (9.1%) patient had Chronic Kidney Disease (CKD). Mean maximum tumor diameter was 7.58 + 0.52 cm, and RENAL score was 9.86 + 1.12. Among them 21 (95.5%) patient were T2aN0M0 (Stage-ii) and 01 (4.5%) T2aN1M0 (Stage-iii). Pre-operative mean serum creatinine was 1.05 + 0.31 mg/dl and eGFR was 86.3+ 21.4 ml/min. After following up for one year the mean serum creatinine and eGFR was 1.0 + 0.24 mg/dl and 88.9 + 19.2 ml/min respectively. No significant alteration observed in concurrent variables like Hb%, ESR, alkaline phosphatase and LDH level. Seventeen cases (77.3%) was found to have clear cell variety of RCC, whereas 02 (9.1%) papillary RCC and 3 (13.6%) chromophobe RCC. While plotted on Clavien-Dindo Classification of post-operative complication, 05 (22.7%) patient developed Grade-1 complication. None of our cases had any recurrence of cancer within the 01 year of follow up. Conclusion: Our study supports expanding the role of partial nephrectomy beyond traditional size limits, demonstrating that even tumors >7 cm can be managed effectively with nephron-sparing surgery in selected patients. When performed in specialized centers, PN offers favorable short-term oncological outcomes while preserving renal function, underscoring its growing importance in modern RCC management. J Bangladesh Coll Phys Surg 2026; 44: 117-126